Pematahan Dormansi Benih Kelapa Sawit (Elaeis guineensis Jacq.) Menggunakan KNO3 dan Skarifikasi - Kartika, .; Surahman, M; Susanti, M (JURNAL ENVIAGRO, 2015)
The study aimed to determine the effect of scarification and soaking in potassium nitrate on breaking of oil palm seed dormancy and to know the best treatment combination of all treatments tested. The experiment was conducted on January2013 to March 2013 in theincubation room at the Village Pagarawan Merawang District.Research using 2x3 factorial arranged in completely randomized design, repeated 8 times. The first factor was scarification treatment that consists of injured seed coat and no injured seed coat. The second factor was chemical treatment that consists of soaking potassium nitrate with a concentration of 0 %, 0.1%, 0.2%. Parameters observed was First Count Germination (FCG),MaximumGrowthPotential,Germination,Seedling growth rates, The rootlength, length ofplumula, Dormancy intensity,Normalembryos. Data were analyzed using variance analysis followed by Duncans Multiple Range Test with α = 5%.The results showed that the average speed of germination treatments (combination of scarification and KNO3)give a mean value of 2.38% growth rate per Etmal. Without scarification with a mean of 1.66 Per Etmal. The best treatment is a combination of the scarification treatment with 0.2% KNO3 concentration had growth rates of 2.56%/Etmal.